Hexafluoroisobutylation of enolates through a tandem elimination/allylic shift/hydrofluorination reaction. Issue 33 (15th August 2022) - Delamare, Aline; Naulet, Guillaume; Kauffmann, Brice; Guichard, Gilles; Compain, Guillaume
Abstract : Hexafluoroisobutylation of ketoesters, malonates, diketones, Schiff base esters and malononitrile is reported. The reaction involves an elimination/allylic shift/hydrofluorination cascade process that efficiently overcomes the usual SN 2′ mechanism. Abstract : The isobutyl side chain is a highly prevalent hydrophobic group in drugs, and it notably constitutes the side chain of leucine. Its replacement by a hexafluorinated version containing two CF3 groups may endow the target compound with new and advantageous properties, yet this modification remains overlooked due to the absence of a general and practical synthetic methodology. Herein, we report the first general method to introduce the hexafluoroisobutyl group into ketoesters, malonates, 1, 3-diketones, Schiff base esters and malononitrile. We demonstrated that the reaction occurs through an elimination/allylic shift/hydrofluorination cascade process which efficiently overcomes the usual fluoride β-elimination observed with α-CF3 -vinyl groups. We showed that with alkali metal bases, a pentafluorinated alkene is obtained predominantly, whereas the use of tetrabutylammonium fluoride (TBAF) allows hydrofluorination to occur. This tandem process represents a conceptually new pathway to synthesize bis-trifluoromethylated compounds. This methodology was applied to the multigram-scale synthesis of enantiopure ( S )-5, 5, 5, 5′, 5′, 5′-hexafluoroleucine.